Sustainable | Sustaining City Streets - Tamminga, Ken; Knüvener, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Streets are an integral part of every city on Earth. They channel the people, vehicles, and materials that help make urban life what it is. They are conduits for the oft-taken-for-granted infrastructures that carry fresh water, energy, and information, and that remove excess stormwater and waste. The very air that we breathe-fresh or foul-flows through our street canyons. That streets are the arteries of the city is, indeed, an apt metaphor. But city streets also function as a front yard, linear ecosystem, market, performance stage, and civic forum, among other duties. In their various forms, streets are places of interaction and exchange, from the everyday to the extraordinary. As the editors affirm, the more we scrutinize, share, and activate sustainable approaches to streets, the greater the likelihood that our streets will help sustain life in cities and, by extension, the planet. While diverse in subject, the papers in this volume are unified in seeing the city street as the complex, impactful, and pliable urban phenomenon that it is. Topics range from greenstreets to transit networks to pedestrian safety and walkability. Anyone seeking interdisciplinary perspectives on what makes for good city streets and street networks should find this book of interest.